2020
DOI: 10.1002/jmv.25668
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of active infection by herpes simplex virus type 2 in patients with high‐risk human papillomavirus infection: A cross‐sectional study

Abstract: The aim is to determine the prevalence of active infection by herpes simplex virus type 2 (HSV‐2) among Mexican women with high‐risk human papillomavirus (HR‐HPV) cervical infection, recruited from public gynecology and colposcopy services. In a cross‐sectional study, HSV‐2 antibodies, HSV‐2 DNA, and HR‐HPV DNA were quantified. Significant differences in HSV‐2 seroprevalence and HSV‐2 active infection rates were found between negative and positive HR‐HPV cases. HSV‐2 seroprevalence was 28.15% and 16.1% (P = .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…( Smith et al., 2002 ) found that HSV-2 seropositivity was associated with increased risks of squamous cell carcinoma (OR 2.19, 95% CI 1.41–3.40) and adeno- and adenosquamous cell carcinomas (OR 3.37, 95% CI 1.47–7.74), after adjustment for potential confounders. A cross-sectional study in 2020 observed significant differences in HSV-2 seroprevalence and HSV-2 active infection rates between negative and positive HR-HPV cases ( Bahena-Román et al., 2020 ). Li et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Smith et al., 2002 ) found that HSV-2 seropositivity was associated with increased risks of squamous cell carcinoma (OR 2.19, 95% CI 1.41–3.40) and adeno- and adenosquamous cell carcinomas (OR 3.37, 95% CI 1.47–7.74), after adjustment for potential confounders. A cross-sectional study in 2020 observed significant differences in HSV-2 seroprevalence and HSV-2 active infection rates between negative and positive HR-HPV cases ( Bahena-Román et al., 2020 ). Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the correlation between HSV-2 and HPV infection and cervical lesions, Smith et al (Smith et al, 2002) found that HSV-2 seropositivity was associated with increased risks of squamous cell carcinoma (OR 2.19,) and adeno-and adenosquamous cell carcinomas (OR 3.37, 95% CI 1.47-7.74), after adjustment for potential confounders. A cross-sectional study in 2020 observed significant differences in HSV-2 seroprevalence and HSV-2 active infection rates between negative and positive HR-HPV cases (Bahena-Romań et al, 2020). Li et al (Li and Wen, 2017) used eight datasets and a sample of 8,184 participants, finding that HSV-2 was associated with cervical cancer after adjusting for HR-HPV (OR adj 1.90, 95% CI 1.09-3.34), suggesting that HSV-2 serostatus may serve as an independent predictor of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have shown the prevalence of co-infection with herpes simplex virus (HSV) among patients suffering from high-risk human papillomavirus (HR-HPV) [ 59 ]. High incidence rates for such co-infections have been observed because of the silent seroprevalence of HSV in approximately 80% of the population worldwide [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The major risk factors behind such an infection have been risky sexual behavior and a previous history of HPV and HSV infection [ 61 ]. A study reported the co-infection with EBV, HPV, CMV, and HSV-1 in patients suffering from diabetes mellitus type 2 (DM2) [ 59 ]. The repercussions of the disease spread were linked to the modification of microbiota components that otherwise control the normal functioning of the human body.…”
Section: Resultsmentioning
confidence: 99%
“…1 Indeed, both HPV and HSV-2 have been reported to be associated with cervical cancer. 2 HPV is a DNA virus that infects cutaneous and mucosal epithelia causing warts or benign lesions. 3 However, the majority of infections resolve clinically after several weeks.…”
Section: Introductionmentioning
confidence: 99%